Avaliação da Associação entre os níveis de HEME e HMGB1 com os Marcadores de Ativação da Coagulação em Crises Agudas na Doença Falciforme - Cardoso, Evilázio Cunha (2019)
Sickle cell disease (SCD) is associated with increased levels of extracellular heme, which has been considered a key mediator of inflammation in this condition. Despite abundant evidence supporting this concept in cell and animal models, very few studies addressed the association of heme levels with SCD severity. Methods: This was a cross-sectional study in patients with acute vaso- occlusive crisis (VOC) evaluating the association between total heme levels and clinical characteristics of VOC. Heme levels were measured in serum at admission and after convalescence (discharge or first return visit to outpatient clinic), and correlated with other clinical and laboratory markers of SCD severity. Results: Twenty-eight admission were included, in 25 patients. Heme levels were similar between admission and convalescence. We did not observe any association between total heme levels with clinical markers such as VOC duration, development of acute chest syndrome or baseline SCD severity score. Mild to moderate correlations were observed between heme levels at admission with hemolysis markers, but not with markers or coagulation (D-dimer) or inflammation (platelet, neutrophil, monocyte counts). Conclusion: In the course of VOC, the pattern of variation in total heme levels in serum is heterogenous, and does not associate with clinical and laboratory markers of SCD severity or inflammatory activity. These results highlight the importance of refining the methods to measure free heme in biological matrices so that the association of heme with inflammation and coagulation in SCD can be confirmed in human studies